Bone Tomahawk [videorecording (DVD)] - Russell, Kurt; Wilson, Patrick, 1973-; Fox, Matthew, 1966- (Image Entertainment, 2015)
Four men from a settlement in the old west must ride to the edge of civilization to find some local townspeople who have been abducted. What they find is an evil beyond imagination and an enemy so brutal, they will never be the same again.